«The security dimension and the Human Rights protection practice in the framework of the implementation of the Lisbon Treaty» - ΔΗΜΗΤΡΙΟΥ, ΧΡΙΣΤΙΝΑ - ΙΓΝΑΤΙΟΣ (2015)
Η έννοια του χώρου ασφάλειας, δικαιοσύνηςκαι ελευθερίας στην Ευρωπαϊκή Ένωση. Ιστορική αναδρομή των συνθηκών.